2018
DOI: 10.3390/medicines6010004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Basic Studies of Natural Products and Their Dental Application

Abstract: The present article reviews the research progress of three major polyphenols (tannins, flavonoids and lignin carbohydrate complexes), chromone (backbone structure of flavonoids) and herbal extracts. Chemical modified chromone derivatives showed highly specific toxicity against human oral squamous cell carcinoma cell lines, with much lower toxicity against human oral keratinocytes, as compared with various anticancer drugs. QSAR analysis suggests the possible correlation between their tumor-specificity and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 114 publications
1
40
0
Order By: Relevance
“…Computational analysis. QSAR analysis of cytotoxicity and tumor-specificity of eighteen 2-styrylchromone derivatives [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] were next performed. Since significant correlation (p<0.05) was found between cytotoxicity against tumor and normal cells, and TS with 139, 472 and 67 chemical descriptors (data not shown), top six chemical descriptors were chosen for QSAR analysis (Figures 4, 5 and 6; Table II).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Computational analysis. QSAR analysis of cytotoxicity and tumor-specificity of eighteen 2-styrylchromone derivatives [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] were next performed. Since significant correlation (p<0.05) was found between cytotoxicity against tumor and normal cells, and TS with 139, 472 and 67 chemical descriptors (data not shown), top six chemical descriptors were chosen for QSAR analysis (Figures 4, 5 and 6; Table II).…”
Section: Resultsmentioning
confidence: 99%
“…The difference (T-N) was used as a tumor-specificity index in the following analyses (21). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] investigated in this study. Hungary) (23), was optimized by CORINA Classic (Molecular Networks GmbH, Germany) with forcefield calculations (amber-10: EHT) in Molecular Operating Environment (MOE) version 2018.0101 (Chemical Computing Group Inc., Quebec, Canada) (24).…”
Section: Calculation Of Potency-selectivity Expression (Pse)mentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that classical anticancer drugs exerted both good effect [extremely higher cytotoxicity against human oral squamous cell carcinoma (OSCC) cell lines than human normal oral mesenchymal cells], and bad effect (potent cytotoxicity against human normal oral epithelial cells) (2,3). Recently, moleculartargeted drugs, such as cetuximab (Cmab) and nivolumab (Nmab) have been approved for the treatment of head and neck cancer in Japan (November 10, 2016).…”
mentioning
confidence: 99%